2023
DOI: 10.1021/acs.est.2c06802
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Polypropylene Face Masks: A Potential Source of Micro/Nanoparticles and Organic Contaminates in Humans

Abstract: We have been effectively protected by disposable propylene face masks during the COVID-19 pandemic; however, they may pose health risks due to the release of fine particles and chemicals. We measured micro/nanoparticles and organic chemicals in disposable medical masks, surgical masks, and (K)N95 respirators. In the breathing-simulation experiment, no notable differences were found in the total number of particles among mask types or between breathing intensities. However, when considering subranges, <2.5 μm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Except for the identified additives, 27–66 additives, each with unknown properties and a confidence level of 4, were detected in each mask (Data set S3). Currently, a few studies have shown that various additives are present in masks. ,, For example, using nontarget analysis, 79 (semi)­volatile additives are determined in 20 masks, and 69 are determined in 60 masks . In addition, though this study identified 213 additives with confidence levels 1 and 2 in masks, many additives remained unidentified.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Except for the identified additives, 27–66 additives, each with unknown properties and a confidence level of 4, were detected in each mask (Data set S3). Currently, a few studies have shown that various additives are present in masks. ,, For example, using nontarget analysis, 79 (semi)­volatile additives are determined in 20 masks, and 69 are determined in 60 masks . In addition, though this study identified 213 additives with confidence levels 1 and 2 in masks, many additives remained unidentified.…”
Section: Resultsmentioning
confidence: 84%
“…In early studies, various additives have been identified in the face masks and microplastics, but the categories and concentrations of the additives vary greatly between the two. This difference may be attributed to the functionality of the plastic products as well as the screening methods used. , The additives in microplastics have been more extensively studied than those in face masks, emphasizing the need to explore the risk of additives in face masks on the marine ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…The AP derivative 2,5-di- tert -butylhydroquinone (DTBHQ), which was found at concentrations up to 121 ng/g lw, has a structure similar to that of synthetic phenolic antioxidants (SPAs). DTBHQ may be a byproduct of SPAs and has been detected in face masks . Besides, the compound 2- tert -butyl-1,4-benzoquinone (TBQ), which was found at concentrations up to 11 ng/g lw, is in the aldehydes and ketones category and is a metabolite of the SPA 2- tert -butyl-4-hydroquinone, which is used as a food additive and is cytotoxic .…”
Section: Resultsmentioning
confidence: 99%
“…GC- and LC-HRMS are advanced techniques commonly used for analyzing the causal toxicants in EDA. GC-HRMS, equipped with an electron ionization source, is frequently used for the analysis of low-polarity toxicants in environmental samples, such as low-polarity PAHs, , steroidal EDCs, and others . Meanwhile, polar toxicants, such as polar EDCs , and antimicrobials, , are generally analyzed by LC-HRMS equipped with electrospray ionization (ESI) or atmospheric pressure chemical ionization (APCI) sources.…”
Section: High-performance Hrms Configurationmentioning
confidence: 99%